2001
DOI: 10.1152/ajpcell.2001.281.1.c166
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nuclear localization sites for COX-2 in vascular endothelial cells

Abstract: We investigated the relationships among expression, activity, and spatial organization of cyclooxygenase (COX-1 and COX-2) in endothelial cells from porcine and human cerebral microvessels and from human umbilical vein. In quiescent cells, COX-1 was detected in the perinuclear zone and the cytoplasm, while COX-2 was mainly a nuclear resident possibly connected with the nuclear matrix. COX-2 immunogold labeling was situated in the nuclear envelope, at the nuclear pores, and in connection with the perichromatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
58
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 46 publications
10
58
0
2
Order By: Relevance
“…The sparse, nonuniform COX-2 immunostaining that seemed to be absent from much of the endothelium and limited to the nuclear or perinuclear regions of the endothelial cells differed markedly from the dense uniform COX-1 immunostaining of the endothelium. A predominantly nuclear or perinuclear pattern of COX-2 immunostaining has been reported previously in vascular endothelial cells (Morita et al, 1995;Parfenova et al, 2001). Parfenova et al (2001) proposed that nuclear/perinuclear localization of COX-2 in unstimulated endothelium may influence its function because they observed increased product formation with increased expression of COX-2 in the cytoplasm of cytokine-treated endothelial cells.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The sparse, nonuniform COX-2 immunostaining that seemed to be absent from much of the endothelium and limited to the nuclear or perinuclear regions of the endothelial cells differed markedly from the dense uniform COX-1 immunostaining of the endothelium. A predominantly nuclear or perinuclear pattern of COX-2 immunostaining has been reported previously in vascular endothelial cells (Morita et al, 1995;Parfenova et al, 2001). Parfenova et al (2001) proposed that nuclear/perinuclear localization of COX-2 in unstimulated endothelium may influence its function because they observed increased product formation with increased expression of COX-2 in the cytoplasm of cytokine-treated endothelial cells.…”
Section: Discussionmentioning
confidence: 61%
“…A predominantly nuclear or perinuclear pattern of COX-2 immunostaining has been reported previously in vascular endothelial cells (Morita et al, 1995;Parfenova et al, 2001). Parfenova et al (2001) proposed that nuclear/perinuclear localization of COX-2 in unstimulated endothelium may influence its function because they observed increased product formation with increased expression of COX-2 in the cytoplasm of cytokine-treated endothelial cells. In the present study, the sparse, nuclear or perinuclear localization of COX-2 may limit its activity such that the COX-2 identified may be insufficient to support 5,6-EET-induced contraction.…”
Section: Discussionmentioning
confidence: 61%
“…Active-transcription factors are localized in nuclear matrix, where signal-transduction mechanism(s) are working [36]. The blockade of enhanced TGF-1-typeI receptor prevented COX-2 and HIF-1α expression in nuclei, consistent with an enhancement of TGF-1/TGF-1-typeI receptor couple, condition necessary for the autoregulatory-loop triggering [41].…”
mentioning
confidence: 76%
“…However, in vivo and in vitro studies in piglets demonstrated that COX-2 also functions in the cerebral vasculature of newborn pigs under basal nonstimulated conditions, thus potentially contributing to cerebral hemodynamics (7)(8)(9)(10)(11). COX-1 and COX-2 proteins were also detected by Western immunoblotting and immunostaining in endothelial cells from neonatal human brain at early passages (10).…”
mentioning
confidence: 99%